COVID-19 therapies and their impact on QT interval prolongation: A multicentre retrospective study on 196 patients. (October 2020) - Bianco, M.; Biolè, C.A.; Campagnuolo, S.; Pietrangiolillo, F.; Spirito, A.; Galluzzo, A.; Nuñez-Gil, I.; Destefanis, P.; Luciano, A.; Carvalho, P.; Varalda, G.P.; Previti, A.; et al.
Abstract: Background: SARS-CoV-2 infection has caused a global pandemic. Many of the medications identified to treat COVID-19 could be connected with QTc prolongation and its consequences. Methods: Non-ICU hospitalized patients of the three centres involved in the study from the 19th of March to the 1st of May were included in this retrospective multicentre study. Relevant clinical data were digitally collected. The primary outcome was the incidence of QTc prolongation ≥ 500 ms, the main secondary outcomes were the Tisdale score ability to predict QTc prolongation and the incidence of ventricular arrhythmias and sudden deaths. Results: 196 patients were analysed. 20 patients (10.2%) reached a QTc ≥ 500 ms. Patients with QTc ≥ 500 ms were significantly older (66.7 ± 14.65 vs 76.6 ± 8.77 years p: 0.004), with higher Tisdale score (low 56 (31.8%) vs 0; intermediate 95 (54.0%) vs 14 (70.0%); high 25 (14.2%) vs 6 (30.0%); p: 0.007) and with higher prognostic lab values (d-dimer 1819 ± 2815 vs 11486 ± 38554 ng/ml p: 0.010; BNP 212.5 ± 288.4 vs 951.3 ± 816.7 pg/ml p < 0.001; procalcitonin 0.27 ± 0.74 vs 1.33 ± 4.04 ng/ml p: 0.003). After a multivariate analysis the Tisdale score was able to predict a QTc prolongation ≥ 500 ms (OR 1, 358 95% CI 1, 076–1, 714p: 0, 010). 27 patients died because of COVID-19 (13.7%), none experienced ventricular arrhythmias, and 2 (1.02%) patients with concomitant cardiovascular condition died of sudden death. Conclusions: In our population, a QTc prolongation ≥ 500 ms was observed in a minority of patients, no suspected fatal arrhythmias have been observed. Tisdale score can help in predicting QTc prolongation.